2020
DOI: 10.1002/aelm.202000205
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Transport in Topological Surface States of Selectively Grown Bi2Te3 Nanoribbons

Abstract: Conventional 3D TIs are the van der Waals bound, binary compounds such as Bi 2 Te 3 , [10] Bi 2 Se 3 , [11,12] Sb 2 Te 3 , [13] as well as alloys of these elements. [14,15] For a quasi 1D nanowire, due to the inclusion of the Berryphase of a particle traversing the perimeter of the nanowire, the surface band structure is determined to be gapped. [16-18] By applying a magnetic flux parallel to the nanowire axis Φ = ±Φ 0 /2, where Φ 0 = h/e, this gap will be closed. The non-degenerate, topologically protected li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 54 publications
3
49
0
Order By: Relevance
“…The transition from 3D topological surface states on each individual surface of the TI and quasi-1D states confined to the perimeter of a narrow TI nanoribbon is sharp, as it is solely dependent on the relation of the phase-coherence length to the nanoribbon perimeter. In previous studies, we found that for 200-nm-wide nanoribbon devices, the topological wave function traverses the perimeter phase coherently, while for devices of width W ≥ 500 nm, this is not observed ( 37 ).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The transition from 3D topological surface states on each individual surface of the TI and quasi-1D states confined to the perimeter of a narrow TI nanoribbon is sharp, as it is solely dependent on the relation of the phase-coherence length to the nanoribbon perimeter. In previous studies, we found that for 200-nm-wide nanoribbon devices, the topological wave function traverses the perimeter phase coherently, while for devices of width W ≥ 500 nm, this is not observed ( 37 ).…”
Section: Resultsmentioning
confidence: 88%
“…We now focus on the investigation of junctions on narrow BST nanoribbons of only W = 200 nm that have been defined using a SAG approach ( 24 , 36 , 37 ). In Josephson junctions on selectively deposited nanoribbons, the geometry of the junction is defined by the width W of the TI nanoribbon and the electrode separation L of the two superconducting electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). These or larger dimensions are experimentally realizable [45]. We use B ⊥ = 20 T such that the wires are in the quantum Hall regime (see Fig.…”
Section: A Occurrence Of Carmentioning
confidence: 99%